The prospect of implementing a community based home telehealth service for chronic care intervention - Lee, Bible (University of Canterbury. Health Sciences, 2013)
Worldwide, the numbers of people living with chronic conditions are rapidly on the rise. Chronic illnesses are enduring and often cannot be cured, requiring a strategy for long term management and intervention to prevent further exacerbation. Globally, there has been an increase in interventions using telecommunications technologies to aid patients in their home setting to manage chronic illnesses. Such interventions have often been delivered by nurses. The purpose of this research was to assess whether a particular intervention that had been successfully implemented in the United Kingdom could also be implemented in Canterbury. In particular, this research assessed the perspectives of Canterbury based practice nurses and district nurses. The findings suggest that a majority of both district and practice nurses did not view the service as compatible with their current work situation. Existing workload and concerns over funding of the proposed service were identified as potential barriers. However, the service was perceived as potentially beneficial for some, with the elderly based in rural areas, or patients with chronic mental health needs identified as more likely to benefit than others. Practice nurses expressed strong views on who should deliver such services. Given that it was identified that practice nurses already have in-depth knowledge of their patients’ health, while valuing the strong relationships established with their communities, it was suggested that patients would most benefit from locally based nurses to deliver any community based health services in the future. It was also found that teletriaging is currently widely used by practice nurses across Canterbury to meet a range of health needs, including chronic mental health needs. This suggests that the scope of teletriaging in community health and its potential and full implications are currently not well understood in New Zealand. Significant events, such as the Christchurch earthquakes indicate the potential role of teletriaging in addressing mental health issues, thereby reducing the chronic health burden in the community.